The Role of Madrasah Working Groups in Improving the Performance of Private Madrasah Teachers in Serang District - Nurlelah; Anis Fauzi; Ahmad Qurtubi; Eneng Muslihah (PT Mattawang Mediatama Solution, 2023)
The madrasah head has the right to mobilize the teachers to participate in the madrasah working group program. On the other hand, teachers must be able to formulate lesson plans, implement learning procedures, and establish interpersonal relationships with students, fellow teachers, education personnel, parents, and stakeholders. Therefore, it is necessary to conduct research on the empowerment of madrasah working groups to encourage improved teacher performance. The approach used in this research is quantitative, which is research that describes each variable. The purpose of using a quantitative approach is to explain the facts. Based on the results of descriptive analysis, it can be seen that there is a tendency for high teacher performance to be followed by a high score of madrasah leadership. This means that there is a tendency for good leadership to support high teacher performance. The conclusions obtained from the results of this study are: First, the better the madrasah principal's leadership, the higher the teacher's performance; on the other hand, poor madrasah leadership has the potential to reduce teacher performance. Second, the higher the work motivation of teachers, the higher the performance of teachers, otherwise teachers with low work motivation tend to have low performance.